Preparation of hierarchical SnS2/SnO2 anode with enhanced electrochemical performances for lithium-ion battery. (1st June 2017) - Yin, Lixiong; Chai, Simin; Huang, Jianfeng; Kong, Xingang; Pan, Limin
Graphical abstract: Abstract: In the work, hierarchical SnS2 /SnO2 composites have been successfully synthesized by a facile one-step solvothermal method. It is found that the basic nature of the solution plays a crucial role in ascertaining the phase and structures of the Sn-based products. And compared with plate-like SnS2 nanoparticles fabricated in deionized water (DI w), the sphere-like SnS2 /SnO2 composites obtained in anhydrous ethanol (AE) exhibit excellent electrochemical performances as anode material for lithium-ion batteries (LIBs). The discharge capacity of SnS2 /SnO2 electrode retains 588.15 mA h g −1 at 100 mA g −1 after 50 cycles, and the discharge capacity of the electrode can still stably reserve 559.16 mA h g −1 even at 800 mA g −1, demonstrating a significantly increased cycling reversibility and structural stability compared to the bare SnS2 . The sphere-like SnS2 /SnO2 structure are assembled by nanoparticles, which can shorten the lithium-ions/electrons pathways, the hierarchical structure of SnS2 /SnO2 composites can accommodate the large volume variation. The charge/discharge performance of the SnS2 /SnO2 composites can also be enhanced by the synergy effects of SnS2 and SnO2 .